Research on the Influence Mechanism of “Scenery-Relics” Landscape on Public Spatio-Temporal Behavior and Perception Preference in Industrial Wasteland: A Case Study of Shougang Industrial Heritage Park - Sijia QIU; Lige BAO; Jing XU; Fang WEI (Fengjing Yuanlin)
ObjectiveDuring the de-industrialization period, large areas of urban industrial wastelands have slowed the process of urbanization and economic development. These sites, associated with environmental pollution, loss of biodiversity, and urban spatial fragmentation, have negatively influenced residents’ quality of life and well-being, eventually turning into abandoned spaces. The reclamation of industrial wastelands can effectively promote the development of these accounting components. Moreover, the “Scenery-Relics” concept, as a novel form of green space, has demonstrated significant potential for transformation, offering new directions for enhancing ecosystem cultural services.MethodsThe spatio-temporal behavioral trajectory technique provides an accurate and efficient method for the research on public behavioral preferences in post-industrial landscapes. Based on the aforesaid technique, to quantify the naturalness of sample spaces, spatial metrics are employed to measure their natural degree. By examining the trajectory patterns of tourists in post-industrial landscapes with varying degrees of naturalness, the number and density of trajectory points are used to investigate the behavioral patterns of tourists.ResultsThe results indicate a significant association mechanism between the spatio-temporal behavior trajectories of tourists and the “Scenery-Relics” of industrial land renewal. Various spatial elements and subjective emotional indicators within the naturalness of industrial landscapes exert certain influence on tourists’ spatio-temporal behavior. Overall, the proportion of buildings is inversely related to tourists’ stay time; the higher the proportion of buildings among all landscape elements, the shorter tourists’ stay. In terms of spatial indicators regarding the naturalness of industrial landscape, there is no significant correlation between behavior distribution and the proportions of paved areas, pedestrian pathways, vehicular roadways, or green spaces. However, the proportion of buildings shows a significant negative correlation with stay behavior distribution, while the proportion of water bodies exhibits a significant negative correlation with traffic behavior. The number of patches is not significantly related to behavior distribution, but the landscape shape index shows a significant positive correlation with strolling behavior. Shannon's Diversity Index and Simpson's Diversity Index demonstrate significant positive correlations with rapid traffic behavior. While naturalness and artificial elements are not significantly correlated with behavior distribution, natural elements show a significant positive correlation with stay behavior, and the number of plant layers is positively correlated with stay behavior. However, the data on subjective emotional indicator do not follow a normal distribution (p＜0.05). Satisfaction, plant species, naturalness, and a sense of security show no significant relationship with behavior distribution. In contrast, artificial interventions and management are significantly positively correlated with stay behavior, indicating that tourists’ subjective perception of Shougang Industrial Heritage Park reveals a significant correlation between artificial interventions, management, and tourists’ behavior trajectories. Additionally, relevant research on the San Gaolu Xiuchi and Qunming Lake areas further confirms that within the natural elements of landscape spaces, the area of water bodies and the richness of plant spatial diversity are positively correlated with tourists’ stay time. Larger water body areas and more diverse plant landscapes can effectively attract tourists to stay.ConclusionExamining the behavior patterns of tourists in post-industrial landscapes from the perspective of spatio-temporal trajectory can help elucidate the spatio-temporal relationships between post-industrial landscapes and tourist behaviors. This approach provides a theoretical reference for the design and transformation of post-industrial landscapes, the optimization of urban green space structure, and the organic renewal of industrial wastelands.